The Influence of Social Media Marketing and Brand Image on the Purchase of Nasa Products at VCN Store Palu - Sarifuddin T; Nasrulhak Akkas; Guasmin; Haris Abd Kadir; Dicky Yusuf (Universitas Muhammadiyah Palu, 2024)
This study aims to analyze the influence of social media marketing and brand image on purchasing decisions at Vidia Cindya Novita Store Palu. This study uses primary data collected through questionnaires from 78 store customer respondents. The data analysis technique uses multiple linear regression. The results of the study indicate that social media marketing and brand image simultaneously have a significant effect on purchasing decisions. Partially, social media marketing and brand image each have a positive and significant effect on purchasing decisions. Social media marketing provides an effective contribution in building brand awareness and influencing consumer attitudes. While a positive brand image can increase consumer trust and preference for a product. In conclusion, social media marketing and brand image are important factors that need to be considered by stores in an effort to improve consumer purchasing decisions.